Strengthening Civic Disposition to Build Civic Engagement and Political Participation in Civic Education in Indonesia - Hidayah, Yayuk; Sujastika, Ismi (Institut Agama Islam Negeri Ponorogo, 2024)
Civic education in Indonesia faces challenges in building civic engagement and political participation among the younger generation. The main issue raised in this study is the importance of civic disposition in shaping the attitudes and behaviors of active citizens. The method used is a literature study that analyzes various academic sources, educational policies, and relevant learning practices. The results of this study show that strengthening civic disposition can be done through an integrative approach, including teaching democratic values, argumentation skills, and developing empathy. The impact of this strengthening can be seen in the increase in political awareness and student participation in social and political activities in their communities. The conclusion of this study confirms that the integration of civic disposition in civic education not only improves students' knowledge but also shapes the character and skills necessary to become active and responsible citizens. This effort is expected to create a younger generation that is more sensitive to social issues and contribute positively to the development of democracy in Indonesia.